Pengembangan Bahan Ajar Digital Berbasis STEM dengan Pendekatan Eco-Spatial Behavior Materi Kependudukan - Dewi, Kusuma; Sumarmi, Sumarmi; Putra, Alfyananda Kurnia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The demands and challenges of 21st century development occur in all areas, especially in the learning process and student competence. The achievement of 21st century learning objectives is implemented in the 2013 curriculum, one of which is through the development of Bahan Ajar Digital (BAD). Development of BAD uses STEM approaches and eco-spatial behavior in Population materials. It is expected to produce students who are able to innovate and compete in the digital age while maintaining environmental sustainability. The development research model uses the ADDIE procedure (Analysis, Design, Development, Implementation, and Evaluation). The data type consists of qualitative and quantitative. Data collection using interview techniques, questionnaires, and documentation with descriptive percentage analysis techniques. The product development trial was conducted in class XII IIS MA Al-Ittihad Poncokusumo. The feasibility test results obtained 87% of student responses, 95% of teacher responses, 90% of material validators, and 95% of media validators. Thus, BAD is very feasible to be used in the learning of Geography.